Difusão do patrimônio audiovisual de televisão pela internet: o caso do Instituto Nacional do Audiovisual (INA) - Ferraz, Bruna Carolina Bueno (2017)
This research aims to study the broadcasting of the audiovisual heritage of television through the internet, based on the case study of the National Institute of Audiovisual (INA), seeking the contributions that the actions of management of the French audiovisual heritage can give professionals of audiovisual collections Brazilians. It analyzes how the access network works and the incentive to use the INA collection over the Internet in order to provide greater democratization of information and knowledge production, highlighting online curatorship focused on the educational function of heritage and the valua-tion of archives.